THE EFFECT OF VERTICAL JUMP EXERCISES ON VOLLEYBALL SMASH ABILITIES - Nur, Ardiansyah; Akhmady, Alief Lam; Bakar, Abu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
The problem of this research is whether there is an effect of vertical jump training on the volleyball smash ability of Luwuk Muhammadiyah University students. This research aims to determine the effect of vertical jump training on volleyball smash ability. The research method used is Quasi-Experiment, while the design is a time series experiment. The subjects of this research were the Muhammadiyah Luwuk Banggai University volleyball team, consisting of 12 athletes. The research results showed that the t value of the initial test and final test of volleyball smash ability was 19.621 and the sig value. 0,000. Because tilapia sig. 0.000 < Î± 0.05, then the alternative hypothesis (H1) is accepted and the Null Hypothesis (H0) is rejected. This means that there is an influence of vertical jump training on volleyball smash ability. The conclusion of this research is that there is an influence of vertical jump training on the volleyball smash ability of the Luwuk Banggai Muhammadiyah University volleyball team.